Two-Switch Forward Converter with Second-Order Sliding Mode Control for High Voltage Battery Management System - Prakash S.; Pandey S.; Ghosh S.; Kamal S. (My University, 2025)
A second-order sliding mode control (SMC) is applied to regulate the third-order two-switch forward converter (FC) in continuous conduction mode which is suitable for wide input voltage range applications e.g. for DC supply to power electronic subsystem in a high voltage Battery Management System (BMS) of Li-ion batteries. The relative degree approach is used for indirect control of output load voltage in the presence of model uncertainties. Super-twisting control is applied to two-switch FC to avoid the disadvantage of chattering effect of first-order SMC. A detailed analysis of modelling and controlling is presented. The converter is simulated with a 550V to 1000V input voltage range to 15V constant output voltage. Simulation results show the advantages of STA such as good transient response and robustness to uncertainties in comparison with the conventional proportional-integral (PI) controller and compensated control system. © 2023 IEEE.